Short- and medium-chain chlorinated paraffins in T-shirts and socks - Tomasko, Jakub; Parizek, Ondrej; Pulkrabova, Jana (Environmental pollution (Barking, Essex, 2023)
The short- and medium-chain chlorinated paraffins (SCCPs and MCCPs) are complex mixtures of persistent compounds used mainly as plastic additives. They can have a negative impact on human health as they are suspected of disrupting the endocrine system and being carcinogenic, which is why monitoring their presence in the human environment is desirable. Clothing was selected for this study because they are produced in large quantities worldwide and the final products are worn for long periods throughout the day, in direct contact with human skin. The concentrations of CPs in this type of sample have not been sufficiently reported. We determined SCCPs and MCCPs in 28 samples of T-shirts and socks by gas chromatography coupled with high-resolution mass spectrometry in negative chemical ionisation mode (GC-NCI-HRMS). CPs were found above the limits of quantification in all samples, with concentrations ranging from 33.9 to 5940 ng/g (mean 1260 ng/g, median 417 ng/g). The samples with a substantial proportion of synthetic fibres contained higher CP concentrations (22 times higher mean for SCCPs and 7 times higher mean for MCCPs) than garments composed exclusively of cotton. Finally, the effect of washing in the washing machine was investigated. The individual samples behaved differently: (i) excessively emitting CPs; (ii) being contaminated; (iii) retaining the original CP levels. The CP profiles also changed for some samples (with a substantial proportion of synthetic fibres and samples composed exclusively of cotton).
Keywords: Chlorinated paraffins; China; parafín; lidé; hmotnostní spektrometrie; Humans; plynová chromatografie s hmotnostně spektrometrickou detekcí; Mass Spectrometry; Gas chromatography; Mass spectrometry; Textile; chlorované uhlovodíky; Environmental Monitoring; monitorování životního prostředí; Paraffin; Gas Chromatography-Mass Spectrometry; Čína; Hydrocarbons, Chlorinated; Endocrine disruptors